Skeletal fluorosis with neurological complications - Dissanayake, J.K.; Abeygunasekara, A.; Jayasekara, R.W.; Ranathunga, C.; Ranathunga, N.V. (Sri Lanka Medical Association, 1994)
A case of skeletal fluorosis with spinal cord compression from Kekirawa following consumption of water with high fluoride content for about 20 years is described. The observations of other workers (4,5) and the present case report show that more extensive field studies among vulnerable populations is indicated in this region. The need to search for a cost effective method of defluoridation of water is stressed.